The psychological and cognitive factors causing college students’ demotivation to learn English in China - Ren, Xiaobin; Abhakorn, Jirapa (Frontiers in Psychology, 2022)
Demotivation is one of the important factors causing students’ failure in learning a language. To explore the psychological and cognitive factors causing college students’ demotivation to learn English in China’s universities and to investigate the relations among these internal factors, this study constructed a shopping cart model by applying grounded theory method and tested the model by using structural equation modeling. This study found three paths underlying students’ demotivation to learn English, originating from large discrepancy between students’ actual and required positioning of English learning, low required positioning of English learning and low value of English learning in students’ minds. Based on these findings, this study gave some pedagogical implications for English teaching.